2014
DOI: 10.1590/1519-6984.17912
|View full text |Cite
|
Sign up to set email alerts
|

Implication of anaerobic and aerobic decomposition of Eichhornia azurea (Sw.) Kunth. on the carbon cycling in a subtropical reservoir

Abstract: This study aimed at describing kinetic aspects of aerobic and anaerobic mineralization of Eicchornia azurea. The samples of aquatic macrophyte and water were collected in the Monjolinho Reservoir (22° 00' S and 47° 54' W). To determine the leachate potential, dried plant fragments were added to reservoir water, with sampling lasting for 4 months, where the particulate and dissolved organic carbon concentrations were measured. The kinetics of mass loss was obtained with 10 mineralization chambers for both aerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…Analysis of the percent mass loss of E. azurea observed in this study reveals that its decomposition ratio was very slow in comparison to others reported in the literature (Pagioro and Thomaz 1998, Stripari and Henry 2002, Padial and Thomaz 2006, Martins et al 2011, Bianchini Jr. et al 2014. In contrast, the half-life (t 1/2 = 468 days) calculated up to the 35 th day of incubation was similar to that reported by Cunha-Santino et al (2010) for refractory fractions of E. azurea (t 1/2 = 385 to 462 days) in the laboratory.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Analysis of the percent mass loss of E. azurea observed in this study reveals that its decomposition ratio was very slow in comparison to others reported in the literature (Pagioro and Thomaz 1998, Stripari and Henry 2002, Padial and Thomaz 2006, Martins et al 2011, Bianchini Jr. et al 2014. In contrast, the half-life (t 1/2 = 468 days) calculated up to the 35 th day of incubation was similar to that reported by Cunha-Santino et al (2010) for refractory fractions of E. azurea (t 1/2 = 385 to 462 days) in the laboratory.…”
Section: Discussionsupporting
confidence: 84%
“…Plant decomposition rates in aquatic environments are controlled by multiple physical, chemical and biological processes (Sangiorgio et al 2010). These processes may be intrinsic or extrinsic, such as the type of decomposition (e.g., aerobic or anaerobic), the enzymatic capacity of the microbial community in the degradation of organic matter, environmental variables (e.g., temperature, availability of dissolved oxygen, pH, redox potential) and detritus quality (Bianchini Jr. et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the methodological procedures used may have interfered with the dynamics of decomposition of E. azurea, as it was slower than in other studies Martins et al 2011;Bianchini et al 2014). Since aquatic plants generally begin to decompose at the senescence stage, part of the labile compounds may have been lost even before incubation in water (Pagioro and Thomaz 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic microcosms were setup in glass bottles (volume 450 ml) with lids wherein 4.0 g plant dry mass were added to 400 ml of filtered water (Gimenes et al, 2013) and 4 ml of microbial indigenous inoculant (based on experiments from . According to Bianchini Jr. et al (2014) based on the kinetics of oxygen consumption during macrophytes decomposition the anaerobic condition was achieved on maximum of 2 h after the introduction of plant fragments in the water. To ensure the anaerobic conditions, after being prepared, the chambers used in the anaerobic processes were closed, being opened only on the sampling days.…”
Section: Anaerobic Decomposition Assaymentioning
confidence: 99%